The Poetic Lyrics of Taylor Swift’s Songs and Its Translation - Guvita Putri Cahyani; Dimas Adika (PRAGMATICA : Journal of Linguistics and Literature, 2025)
Lyrics is a crucial part of the song, it usually contained by the message from the songwriter, it can created from imagination, moral message or personal experience and so on. The songwriter itself have their own style to create the lyrics. Some lyrics came with outspoken and some came with implicit way to convey what’s the songwriter aim’s. This research was made to identify poetical sentence contained in several Taylor Swift’s lyric song, also to find out the meaning behind the lyrics written. This research used a qualitative method with collecting poetical sentence contained in three different song from Taylor Swift’s newest album called The Tortured Poets Department; The Anthology, then translated into Indonesian as a target language (TL). In this research also conclude about how importance of translating song lyrics appropriately and acceptably for the audience without losing the message from songwriter, where in this case the songwriter uses poetic sentence to convey the interpretation of thought and feeling of the songwriter.